Covid-19 Pandemic Impact on the Deteriorating Street Function - Marina Mohd Nor; Norzailawati Mohd Nor (International Journal of Agricultural Sciences, 2021)
Since the pandemic hit the globe in 2020, it has changed the street's image. The street remains silent due to the COVID-imposed lockdown. The streets, usually bustling with people and activities, were near silent. The commencement practice of "social-distancing" has brought dramatic changes in street usage, where streets portray as a place for active travel, mobility, and connecting people. Thus, this paper reviews the present effect of changing street behavior based on existing literature. Qualitative analysis was performed using content analysis to elaborate on the impact of street function during this pandemic. Activities on the street such as walking, cycling, gathering, and social events have impacted and limited participation in public. However, the street plays a vital role in supporting physical and mental well-being, as mentioned in SDG 11: Make the cities and human settlements inclusive, safe, resilient, and sustainable. The findings of this study will help ensure that streets can become a public health approach and risk reduction for people to engage in outdoor activities. Therefore, streets serve as the primary hope in overcoming the pandemic and how the city and people can have inclusive and safe access to the streets throughout the pandemic. We believe that social distancing should not preclude social interaction.